Cardiovascular risk following metformin treatment in patients with type 2 diabetes mellitus: Results from meta-analysis. (February 2020) - Zhang, Kui; Yang, Wenxing; Dai, Hao; Deng, Zhenhua
Abstract: Aim: Pharmacologic therapy for T2DM has proven benefits in terms of reducing elevated blood glucose levels and reducing microvascular complications. However, the impact of metformin on adverse cardiovascular outcomes and cardiovascular mortality is less clear. We carried out this meta-analysis on all published studies to estimate the overall cardiovascular risk following metformin treatment in patients with T2DM. Methods: We searched the PubMed, Embase and CNKI (China National Knowledge Infrastructure) databases for all articles. The odds ratio (OR) corresponding to the 95% confidence interval (95% CI) was used to assess the cardiovascular risk following metformin treatment in patients with T2DM. The statistical heterogeneity among studies was assessed with the Q-test and I 2 statistics. Results: We collected 16 studies including 25 comparisons with 1, 160, 254 patients of type 2 diabetes mellitus and 701, 843 patients of T2DM following metformin treatment. Our results found statistical evidence of significantly decreased cardiovascular risk to be associated with following treatment with metformin in patients with type 2 diabetes mellitus (OR = 0.57, 95% CI = 0.48–0.68) (shown in Table 1 and Fig. 2), both with the mortality (OR = 0.44, 95% CI = 0.34–0.57) and incidence (OR = 0.73, 95% CI = 0.59–0.90). Conclusions: Our meta-analysis indicated that following metformin treatment in patients with T2DM was associated with decreased cardiovascular risk, both with the mortality and incidence. However, the heterogeneity among studies may potentially affect the final results.